Efforts to Improve Number Recognition Skills through the Use of Number Cards in Children at RA Al-Ihsan - Hertati, Heti (Jurnal Profesi Guru Indonesia, 2025)
Early childhood is a period of development from 2 to 6 years of age which is marked by rapid physical growth, language development, and increased symbolic thinking skills. Early childhood education aims to develop various aspects of child development, including cognitive abilities, which include the introduction of simple science and mathematics concepts. Mathematics learning for early childhood needs to be done contextually and interestingly so that children can understand the concept of numbers optimally. Based on the results of observations at RA Al-Ihsan, it was found that children's ability to recognize the concept of numbers is still low. Of the 20 students in group A, only 10 students (50%) have recognized numbers, while the other 10 students (50%) have not. This problem is caused by the learning method which is still centered on the teacher and the lack of use of appropriate learning media. This study aims to improve students' ability to recognize numbers through the use of number cards. This media can help children understand the concept of numbers in a more interactive and fun way. By using the classroom action research (CAR) method, this study is expected to provide solutions in improving children's understanding of numbers and improving learning methods at RA Al-Ihsan.